Ógle Wakȟáŋ Kiŋ: Relational materiality and the Lakota Ghost Dance of 1890. (3rd July 2022) - Jansson, Fredrik
Abstract : This article examines the materiality of the Ghost Dance shirt – ógle wakȟáŋ kiŋ – among the Lakota, and its associated symbols and functions. By cross-referencing sources on the Ghost Dance to sources on traditional Lakota belief and ritual, it is shown that the practice of interrituality – the use of established ritual elements and acts in novel contexts – enabled traditional ritual dynamics and ontological understandings to be actualized and materialized in the Ghost Dance. This gave it performative powers and a sense of cultural familiarity with which participants could navigate a turbulent period with recognizable ritual elements. Considering the primacy of visions, concepts such as wakȟáŋ, wašíčuŋ, tȟúŋ, and wótȟawe, protective designs, and ritual processes, the article problematizes a tradition-innovation dichotomy, suggesting instead that ritual materiality mediated between the two. Likewise, it is argued that the protective nature of the shirts was primarily existential and spiritual rather than exhibitions of militarism.